An exploratory social media intervention for perception and behavior on eating away from home: A cluster randomized trial in Chongqing, China. (1st May 2022) - Wu, Tingting; Hu, Ping; Zou, Mao; Zhang, Fan; Zeng, Huan; Sharma, Manoj; Zhao, Yong; Shi, Zumin
Abstract: A modern diet with high energy density is harmful to health and negatively affects the environment. Eating out is particularly prevalent among young adults and has steadily increased in many countries over the last few decades. This study aims to assess the impact of nutrition education interventions on social media on cognitive and behavioral changes in the diet of university students. A cluster-randomized trial with an intervention group (n = 853) and a no-intervention control group (n = 846) was conducted in Chongqing. A two-month educational intervention was conducted through social media (WeChat official account, Sina Weblog, and Tencent Weibo) with participants of the intervention group. Self-reported eating-out-related knowledge and behaviors were assessed at baseline and six and eight months after randomization. Multilevel mixed-effects logistic regression and linear regression analyses accessed the outcomes between the intervention and control groups. The proportion of participants in the high-level knowledge and attitude group in the intervention group increased by 13% and 8.5% compared with the control group (p < 0.05). The effects of the intervention on the outcomes significantly changed over time, as demonstrated by the achieved statistical significance for knowledge and attitude score (p for group and time interaction <0.001) in the interaction between time and randomization groups. The high-frequency eating away from home/school at weekends decreased from 29.6% to 27.3% in the intervention group. In the control group, the high-frequency eating away from home/school at weekends in the increase was increased (26.3%–27.2%). A total of 73.6% of respondents in the intervention group reported that they consciously reduced their frequency of eating away from home/school. The possibility exists for narrowing the perception and behavior disparity gap through the effective use of social media, such as WeChat and Microblog, which could be a sustainable platform to provide health education or new food policies to promote healthy eating and reduce food waste among university students. Highlights: Frequent eating away from home/school is common in young Chinese adults. Social media intervention is effective in reducing the frequency of eating away from home/school among young adults. The long-term effect of social media intervention is unknown and warrants further research. Social media intervention provides a new direction on reducing food waste problems.